Edukasi Dukungan Psikososial, Spiritual Dan Mitigasi Bencana - Nuraisya, Wahyu; Asiyah, Siti; Florentis Yustanta, Brivian; Ertiana, Dwi (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
Natural disasters can disrupt and threaten environmental damage, property loss, and psychosocial impacts on disaster victims. Unpreparedness for community mitigation and psychosocial imbalance affect their physical condition, environment, emotional development and behavior in their survival. The purpose of this service is to provide education on psychosocial and spiritual support in disaster-prone areas and disaster mitigation. This service activity is carried out using psychosocial and spiritual support materials. The media used are kit materials, power points, laptops, mics, and LCDs. This activity was carried out at the Sempu village hall in the working area of ​​the Ngncar Health Center UPTD, Kediri Regency on October 14 - November 02, 2024. The target of the activity is the Village Head, Village Midwife and 33 village cadres. The level of knowledge and ability of participants in understanding educational materials in the post-test results mostly increased to 60.6% from the good category which was originally 0%. Achievement of the objectives is the success of the implementation of community service activities. Cross-sector and cross-program collaboration between education, village heads, midwives and cadres greatly supports efforts to improve the quality of community resources related to disaster management before, during and after disasters as well as handling psychosocial and spiritual imbalances due to the impact of disasters.